Floral Longevity of Paphiopedilum and Cypripedium Is Associated With Floral Morphology - Zhang, Feng-Ping; Feng, Jing-Qiu; Huang, Jia-Lin; Huang, Wei; Fu, Xue-Wei; Hu, Hong; Zhang, Shi-Bao (Frontiers in Plant Science, 2021)
Floral longevity (FL) is an important trait influencing plant reproductive success by affecting the chance of insect pollination. However, it is still unclear which factors affect FL, and whether FL is evolutionarily associated with structural traits. Since construction costs and water loss by transpiration play a role in leaf longevity, we speculated that floral structures may affect the maintenance and loss of water in flowers, and therefore FL. Here, we investigated the slipper orchid Paphiopedilum and Cypripedium, which are closely related, but strongly differ in their FL. To understand the evolutionary association of floral anatomical traits with FL, we used a phylogenetic independent comparative method to examine the relationships between 30 floral anatomical traits and FL in 18 species of Paphiopedilum and Cypripedium. Compared with Paphiopedilum species, Cypripedium species have lower values for floral traits related to drought tolerance and water retention capacity. Long FL was basically accompanied by the thicker epidermal and endodermal tissues of the floral stem, the thicker adaxial and abaxial epidermis of the flower, and low floral vein and stomatal density. Vein density of the dorsal sepals and synsepals was negatively correlated with stomatal density. Our results supported the hypothesis that there was an evolutionary correlation between FL and floral anatomical traits in slipper orchids. The ability to retain water in the flowers was associated with FL. These findings provide a new insight into the evolutionary association of floral traits with transpirational water loss for orchids under natural selection.